Insurance specifics within the FIDIC "Red Book": Conditions of contract for building and engineering works designed by the employer (1st ed. 1999) - Živanović Filip M. (Strani pravni život, 2023)
The subject of this paper is the analysis of the application of the FIDIC "Red Book" -Conditions of contract for building and engineering works designed by the employer (hereinafter: FIDIC Red Book (1999)) in the context of insurance contracting obligations. Special attention is given to the specifics of the conditions of the contract mentioned here, given their terminological and conceptual features, bearing in mind that they come from the COM-mon law system, which has a characteristic approach to the construction insurance. In this regard, the approach of the editor of the FIDIC Red Book (1999) in structuring the provisions dealing with insurance is analyzed, as well as the norms that define the rights and obligations of the contracting parties regarding the provision of insurance.